Development of Predict-Observe-Explain Oriented e-Module as a Learning Media to Improve Students’ Problem Solving Skills - Lihawa, Ernawati Jakaria; Latjompoh, Masra; Baderan, Dewi Wahyuni Kyai (FKIP Universitas Lampung, 2022)
This study aimed to develop POE oriented E-Module with Flip Pdf Professional to practice students’ critical thinking skill on environmental changes materials which is valid, practical, and effective. The subject of this study is the students in grade X IPA5 in SMA Negeri 1 Gorontalo. This study is a research and development. The result of this study revealed that the validity test based on the expert validation analysis (content and construction) and practitioners’ validation (teachers) obtained the x score respectively 96%, 95%, and 95% (very valid). Practicality test as the result of the implementation of teaching and learning, students’ activities and responses obtained x score respectively 100%, 89.28%-92.85%, 95% (very practical). The effectiveness test based on the analysis of N-Gain score in a small group obtained a score as big as 0.78 (effective). It can be concluded that the POE oriented E-Module with Flip Pdf Professional to practice students’ critical thinking skill is considered valid, practical, and effective to be used in Biology class for Grade X in SMA Negeri 1 Gorontalo. Keywords: e-module, predict, observe, explain, critical thinking skills. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp474-485